Interpreting Life Values in The Performance of Ramayana Shadow Puppet Setubanda Play - Marajaya, I Made (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
Ramayana Shadow Puppet Performance is a type of Balinese shadow puppet from the Ramayana Epic, and its position still exists in society today. The Ramayana Shadow Puppet Performance's main characters are Rama a symbol of good and Ravana a symbol of evil. The characters consist of humans, monkeys (ore), and giants. This performance of Ramayana story is famous for its characteristic "ngore" (monkey sound). One of the most popular plays show is Setubanda play, named Sundara Kanda. The shadow puppet play tells the story of Rama's army led by Sugriwa was building a connecting bridge from Mount Mahendra to Alengka. The Setubanda Bridge which had been completed by Rama's troops was then damaged by Ravana's son Detya Kala Sura Bhuta and his crocodile army. Then there was a war that ended with the death of Detya Kala Sura Bhuta. This research used qualitative methods and was supported by semiotic and hermeneutic theories. It can be philosophically interpreted as a bridge between Paramatman (Rama) and Jiwatman (Sita) who were separated by Ravana. The Setubanda play contains many life values; the value of education, leadership, unity, loyalty, and the value of solidarity.